Syndrome of Remitting Seronegative Symmetrical Synovitis with Pitting Edema (RS3PE) - Fatma Paksoy,; Turgay Ulaş,; Emrah Erkan Mazı,; Ayda Batuan Damar,; Fatih Borlu, (Archives of Rheumatology, 2010)
RS3PE (remitting seronegative, symmetric synovitis with pitting edema) is a benign, seronegative syndrome, with an acute onset of pitting edema on the dorsum of both hands and feet, which affects predominantly peripheral joints such as wrists and ankles symmetrically. A 58-year-old man presented with acute symmetrical polysynovitis of the wrists and ankles associated with pitting edema on the dorsum of the both hands and feet. He responded well to low-dose corticosteroids. There was no evidence of erosion radiologically. The clinical manifestations of the patient were consistent with RS3PE syndrome. Here, we present a case of RS3PE and review the literature. (Turk J Rheumatol 2010; 25: 88-90)